Evaluation of four biostimulants for the induction of systemic resistance in cucumber (Cucumis sativus L.) and tomato (Solanum lycopersicum Mill.) in monoculture and associated greenhouse cultivation - Julio Gabriel-Ortega; Pablo Chonillo Pionce; Washington Narváez Campana; Tomas Fuentes Figueroa; Fernando Ayón Villao (Journal of the Selva Andina Research Society)
In order to evaluate four biostimulants in the induction of systemic resistance in cucumber (Cucumis sativus L.) and tomato (Solanum lycopersicum Mill.) in monoculture and associated greenhouse cultivation, five treatments were applied at three developmental stages (growth, flowering and fruiting): T1 Bioremedy (2.0 g/L), T2 Grandsil (2.0 g/L), T3 Control (water), T4 Fossil (5.0 g/L), T5 L-amino (2 cm3/L). The treatments were distributed in a 3 x 5 factorial arrangement and evaluated in a completely randomised experimental design. Each experimental unit consisted of three rows. The response variables were: plant height (cm), stem diameter (mm), number of fruits per plant, fruit volume (cm3) and fruit weight (kg). The results, cucumber in monoculture did not present notable differences for any of the evaluated variables, with the exception of plant height, significant differences were observed at P<0.05 of probability, Bioremedy, L-amino and control were the best. In tomato monoculture, there were significant differences at P<0.05 for all the variables, with Bioremedy standing out for plant height, stem diameter, fruit weight, fruit diameter and fruit number. In the associated crop, both cucumber and tomato had significant differences at P<0.05 for all the variables evaluated, with Bioremedy being the best.